Accuracy of Curable Sexually Transmitted Infections and Genital Mycoplasmas Screening by Multiplex Real-Time PCR Using a Self-Collected Veil among Adult Women in Sub-Saharan Africa. (15th July 2019) - Nodjikouambaye, Zita Aleyo; Compain, Fabrice; Sadjoli, Damtheou; Mboumba Bouassa, Ralph-Sydney; Péré, Hélène; Veyer, David; Robin, Leman; Adawaye, Chatté; Tonen-Wolyec, Serge; Moussa, Ali Mahamat; Koyalta, Donato; Belec, Laurent
Abstract : Background . Sexually transmitted infections (STIs) are highly prevalent in sub-Saharan Africa. Genital self-sampling may facilitate the screening of STIs in hard-to-reach remote populations far from large health care centers and may increase screening rates. The cross-sectional GYNAUTO-STI study was carried out to assess the performance of a novel genital veil (V-Veil-Up Gyn Collection Device, V-Veil-Up Pharma, Ltd., Nicosia, Cyprus) as a genital self-sampling device to collect genital secretions to diagnose STIs by molecular biology as compared to reference clinician-collected genital specimens, in adult African women. Methods . Adult women living in N'Djamena, the capital city of Chad, were recruited from the community and referred to the clinic for women's sexual health " La Renaissance Plus ". A clinician obtained an endocervical specimen using flocked swab. Genital secretions were also obtained by self-collection using veil. Both clinician- and self-collected specimens were tested for common curable STIs (including Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, and Trichomonas vaginalis ) and genital Mycoplasma spp. by multiplex real-time PCR (Allplex™ STI Essential Assay, Seegene, Seoul, South Korea). Test positivities for both collection methods were compared by assessing methods agreement, sensitivity, and specificity. Results . A total of 251 women (mean age, 35.1 years) were prospectively enrolled. Only seven (2.8%) women were found to be infected with at least one common STIs [ C. trachomatis : 3 (1.2%), N. gonorrhoeae : 1 (0.4%), M. genitalium : 4 (1.6%) and T. vaginalis : 1 (0.4%)], while the prevalence of genital mycoplasmas was much higher (54.2%) with a predominance of Ureaplasma parvum (42.6%). Self-collection by veil was non-inferior to clinician-based collection for genital microorganisms DNA molecular testing, with "almost perfect" agreement between both methods, high sensitivity (97.0%; 95%CI: 92.5-99.2%), and specificity (88.0%; 95%CI: 80.7-93.3%). Remarkably, the mean total number of genital microorganisms detected per woman was 1.14-fold higher in self-collected specimens compared to that in clinician-collected specimens. Conclusions . Veil-based self-collection of female genital secretions constitutes a convenient tool to collect in gentle way cervicovaginal secretions for accurate molecular detection of genital bacteria. Such sampling procedure could be easily implemented in STIs clinics in sub-Saharan Africa.